2020
DOI: 10.1111/ajd.13486
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of water as the neutralising agent for glycolic acid peels in skin phototypes IV‐V

Abstract: The aim of the study is to evaluate the effectiveness of water as a substitute for sodium bicarbonate plus solution in the neutralisation process of chemical peeling using a 35% glycolic acid solution. This randomised, double-blind, split-face, controlled trial was conducted in an outpatient setting. A total of 126 healthy patients with skin phototypes IV-V aged between 18 and 60 years old were recruited. Chemical peeling was performed with 35% glycolic acid solution. One side of the face was neutralised with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…Therefore, we speculated that the efficacy of adapalene application in disseminated facial verruca plana is limited; however, its specific effects require further investigation. Third, the Fitzpatrick skin types of patients enrolled in our study were types III and IV, and previous studies supported the claim that the application of 35% GA is safe among patients with this skin type 19 . In future studies, the GA concentration for chemical peels may need to be adjusted for patients with different Fitzpatrick skin types.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Therefore, we speculated that the efficacy of adapalene application in disseminated facial verruca plana is limited; however, its specific effects require further investigation. Third, the Fitzpatrick skin types of patients enrolled in our study were types III and IV, and previous studies supported the claim that the application of 35% GA is safe among patients with this skin type 19 . In future studies, the GA concentration for chemical peels may need to be adjusted for patients with different Fitzpatrick skin types.…”
Section: Discussionsupporting
confidence: 78%
“…Third, the Fitzpatrick skin types of patients enrolled in our study were types III and IV, and previous studies supported the claim that the application of 35% GA is safe among patients with this skin type. 19 In future studies, the GA concentration for chemical peels may need to be adjusted for patients with different Fitzpatrick skin types.…”
Section: Discussionmentioning
confidence: 99%
“…A recent randomized split face study found water can potentially use as a substitute for sodium bicarbonate plus solution in the neutralisation of 35% glycolic acid solution. 27 Various clinical trials have shown the effectiveness of other chemical peelings, such as Jessner peel, lactic acid, pyruvic acid, trichloroacetic acid (TCA), amino fruit acid (AFA), pyruvic acid, and mandelic acid. Jessner peel contains 14% resorcinol, 14% SA, 14% lactic acid, and 95% ethanol 95 which acts as keratolytic, antibacterial, and antiinflammatory agent.…”
Section: Chemical Peelingmentioning
confidence: 99%

Adjuvant therapies of acne: review of literatures

Randy Satria Nugraha Rusdy,
Lili Legiawati,
Irma Bernadette Simbolon Sitohang
et al. 2023
BDVAJ